Association between psychological distress and liver disease mortality: a meta-analysis of individual study participants - Russ, Tom C.; Kivimäki, Mika; Morling, Joanne R.; Starr, John M.; Stamatakis, Emmanuel; Batty, G. David (Elsevier, 2015)
Background & Aims: Risk factors for cardiovascular disease, such as obesity and hypertension, have been associated with non-alcoholic fatty liver disease. Psychological distress (symptoms of anxiety and depression) is a risk factor for cardiovascular disease, so it might also be associated, directly or indirectly, with elevated rates of liver disease. We investigated the relation of psychological distress (measured by the 12-item General Health Questionnaire; GHQ) with liver disease mortality.